Optimalisasi Usaha Industri Kreatif Penyandang Disabilitas - Sudi Dul Aji; Hena Dian Ayu; Hestiningtyas Yuli Pratiwi; Akhmad Jufriadi; Muhammad Nur Hudha (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
This service aims to improve the economy and independence of the creative industries of people with disabilities. The creative industry is a printing and screen printing business owned by partners, namely people with disabilities, especially people who are deaf or hard of hearing and speech impaired. People with disabilities generally find it challenging to get access to funds because their limitations make it difficult to gain trust from the industry. The method offered in implementing this service is transferring science and technology for business development through discussions, guidance, sewing t-shirts and bags, marketing management training, and partner mentoring. Results from questionnaires and partner interviews show that understanding, skills, independence, and the number of products made have increased. In real terms, this service program has succeeded in increasing the turnover of partners. This phenomenon is because partners can receive screen printing and sewing totes and mug accessories simultaneously without going from second-hand (totes and accessories are no longer ordered by other tailors). Thus, this service can help the creative industries of people with hearing and speech impairments become more independent in their society.